(3HMhK GdYedjGJ hJWHjbGJgG GdGbJUGOjI (B:s (3GdHQeLI GdQjGVjI GdLRA GdChd (B/s - (3ecjO, Ydjs ((3GdLRGFQ (B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2011)
(3jVe GdHQeLI GdNWjI , Md GdfeGPL GdNWjI HGSJYeGd GdWQjbI GdHjGfjI, Md GdfeGPL HGSJYeGd GdWQjbI GdSeHdcS, GdMGdGJ GdNGUI dWQjbI GdSeHdcS, GdeSCdI GdKfGFjI aj GdHQeLI GdNWjI, GdHQeLI GdHGQGejJQjI, MSGSjI OGdI GdgOa ddJZjQ aj eYGedGJgG, OQGSI JCKjQ JZjQ GdWQa GdCjef ddbjhO GdafjI, GdHQeLI GdOjfGejcjI hJPcjQ HCge GdbhGYO GdfXQjI, JWHjbGJ fehPL GdHQeLI GdOjfGejcjI(B.s
(3GdeQGLY U(B.343s
Keywords: (3GdHQeLI GdNWjIs; (3GdHQeLI GdQjGVjIs; (3HMhK GdYedjGJs